Should You Breed Cows during the Summer in the Southeastern United States? An Economic Analysis of a Dairy Herd in Florida - Klibs N. Galvão; Albert De Vries (EDIS, 2014)
In the southeast United States, since dairy cows experience decreased reproductive performance during the hot and humid summers, some dairy farmers delay breeding until the cooler fall. But there is no economic data to support this practice. This 3-page fact sheet presents the results of a recent paper that evaluated the effects that delaying breeding during the summer has on cow performance and profitability in Florida. Written by Klibs N. Galvão and Albert De Vries, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, July 2014.